Qualidade de Manga Tommy Atkins Orgânica Colhida sob Boas Práticas Agrícolas, Tratada com Extrato de Erva-Doce e Fécula de Mandioca - Lima, Antonia Barbosa de (2007)
This work, carried out in two experiments, had as objective to evaluate the quality of organic ‘Tommy Atkins’ mango, for exportation, from Fazenda Pernambucanas, located at the Municipal District of São Mamede, Sertão Paraibano region, harvested with (WGP) and without (WOGP) Good Agricultural Practices, in the commercial maturity stage, whose skin color was characterized by shades of green, red, and yellow. Fruits WGP and WOGP were combined with anise (A) extract at 3% (WGP+A, WOGP+A), with anise (A) extract + cassava (C) starch at 1,5% (WGP+A+C, WOGP+A+C), and fruits without anise extract and without cassava starch (WGP, WOGP), control, kept at 10oC, and evaluated each 3 days, during 15 days. For the first experiment it was evaluated the maturation physiology, and for the second, it was evaluated the postharvest conservation of treated fruits. The results were submitted to variance analyzes, when verified significant interaction by the F test at 5% of probability it was submitted to polynomial regression. For the first experiment, anise extract applied direct to the fruit anticipated the respiratory peak, increasing its intensity, mainly for fruits harvested without Good Agricultural Practices (GAP). The use of GAP reduced the rate of starch degradation and the consumption of soluble sugars, reduced the chlorophyll degradation, and kept the carotenoids higher. For the second experiment, anise (A) extract applied directly to the skin at 3%, negatively interfered in the appearance of organic ‘Tommy Atkins’ mango, effect that was minimized when A was applied in combination with cassava starch solution at 1.5%, mainly when associated to GAP. Fruits WOGP presented red-yellowish color as the storage period advanced and in higher intensity as compared with WGP. The use of GAP was determinant in maintaining the good appearance of organic ‘Tommy Atkins’ mango. Fruits harvested with GAP, without combination with treatments, were the most accepted by the judges.